การรับรองการใช้สิทธิเลือกตั้งของผู้ต้องขัง - มนชนก เกิดแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Suffrage is considered to be greatly important in the system of democracy as it is considered a tool for the use of the highest powers of the people who own sovereignty, and it is something that reflects the needs of the people on how the state should proceed to solve the country’s problems. Even though internees have become individuals with restricted liberty and rights in life and body due to offences and violations against the state’s regulations, the liberty and rights of internees should still be accepted and protected according to the law as internees still have rights as the country’s citizens. In the present, Thailand has developed the acceptance of internee suffrage in various areas in the constitution of 2007. However, there are still some rights that are restricted due to their status as internees, which include the civil rights of internees, especially suffrage. In Thailand, there are still no developments to the aforementioned acceptance of rights even though civil rights are considered to be fundamental rights of countries that are ruled by democracies. Thus, restricting the voting rights of individuals should be considered as an exception from general concepts, and rights should only be limited in cases with firm reasons. The state must be rigorous in the legislation of suffrage restricting laws, that is, laws should only be determined as much as necessary for suffrage to cover the people as much as possible. In Thailand, there was a determination of characteristics of individuals with forbidding characteristics to prevent their suffrage usage in the Constitution of the Kingdom of Thailand, clauses 100 and 100(3), which decreed that internees convicted by court or approved lawful decrees were individuals without suffrage on election days, which was a restriction of internee suffrage with the characteristics of general restrictions of rights without considerations of the internees’ offenses and the received rate of penalty anyhow. This results in the implicit loss of suffrage whenever one becomes an internee, including the loss of other political rights as a consequence of the inability to utilize voting rights. From studies of compiled concepts, related theories, and studies of forms of countries that have accepted the usage of internee suffrage, legislative amendments of laws that restrict internee suffrage in Thailand is appropriate, from the general legislated restrictions of internee suffrage to the general enfranchisement of internee suffrage, and only restrict suffrage for internees that have committed offenses related to elections or used suffrage antagonistically to the system of democracy, for internees to still be able to use their own rights as a citizen of the country and for the good of a democratic rule.